Vooronderstellings in die verstaansproses met spesifieke verwysing na Heinrich Ott se Christologiese model - Robbertze, M. D. (Hervormde teologiese studies, 1991)
Presuppositions in the hermeneutical process, with spesific reference to the christological model of Heinrich Ott This article strives to examine the characteristics of the interpretation process, as well as the role that presuppositions play in it. A conclusion is reached that presuppositioniess interpretation does not exist. Interpretation can only be scientifically true if we are aware of our presuppositions, and if we articulate them clearly. A final decisive interpretation is therefore out of the question. This does not entail relativism, it rather involves a multiplicity of viewpoints with relation to a specific issue. In order to illustrate how presuppositions play a role in the interpretation process, there follows an examination of philosophical conceptions - specifically the existential philosophy - in the christological model of Heinrich Ott as expounded in his Die Antwort des Glaubens.